2005
DOI: 10.1097/01.mlg.0000154741.25443.fe
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Esophagoscopy: Revisited (over 700 Consecutive Cases)

Abstract: TNE is safe, well tolerated by patients, and is easy to learn with a short learning curve. TNE may replace radiographic imaging of the esophagus in otolaryngology patients with reflux, globus, and dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
127
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 8 publications
8
127
1
4
Order By: Relevance
“…In Postma's series, 17 procedures were aborted secondary to a tight nasal vault and two were aborted secondary to vasovagal responses. 3 Similarly, a review by Koufman et al of 443 cases of OBFES, which included the use of the laser, revealed a minor complication rate of 0.9% and concluded that unsedated laryngeal surgery with the laser is a safe and effective treatment option. 4 However, neither of these studies, demonstrating overall safety and efficacy, provided data regarding the patients' hemodynamic status during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In Postma's series, 17 procedures were aborted secondary to a tight nasal vault and two were aborted secondary to vasovagal responses. 3 Similarly, a review by Koufman et al of 443 cases of OBFES, which included the use of the laser, revealed a minor complication rate of 0.9% and concluded that unsedated laryngeal surgery with the laser is a safe and effective treatment option. 4 However, neither of these studies, demonstrating overall safety and efficacy, provided data regarding the patients' hemodynamic status during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…1,[5][6][7][8] Because of its small caliber, ability in air insufflation, and the inherence of instrument channel for suction and biopsy, unsedated transnasal esophagoscopy or EGD may overcome the aforementioned difficulties in diagnosis of hypopharyngeal cancer and may be a promising standard diagnostic tool for hypopharyngeal cancer. Reviewing previous studies on the application of unsedated transnasal esophagoscopy or EGD in otolaryngology; however, most investigations have focused on benign diseases, such as globus pharyngius, reflux esophagitis, esophageal foreign body, or placement of the tracheoesophageal puncture.…”
mentioning
confidence: 99%
“…[5][6][7]9,10 Only a limited number of studies have limited experience about the role of unsedated transnasal esophagoscopy or EGD in head and neck oncology. 6,9,11,12 In this article, we provide a detailed report on the efficacy and safety of unsedated transnasal EGD in the diagnosis of hypopharyngeal cancer and screening of simultaneous esophageal lesions.…”
mentioning
confidence: 99%
“…The use of TNO in the investigation of globus and nonprogressive dysphagia is widely accepted internationally, with limited use in the UK. 12 Its use was first described in 1994 by Shaker and since then its use has increased, particularly in the US and Japan. 13 It requires local anaesthesia only, without sedation, and allows visual examination from the nasal cavity to the oesophagogastric junction.…”
Section: Sanyaolu Jemah Stew Ingrams the Role Of Transnasal Oesophagomentioning
confidence: 99%